If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12=12(z-1/3
We move all terms to the left:
12-(12(z-1/3)=0
We add all the numbers together, and all the variables
-(12(+z-1/3)+12=0
We multiply all the terms by the denominator
-(12(+z-1=0
| X+3x-43=-67 | | (m+300)/4=96 | | 10=20+5n | | 6x+4(-3x-16)=-28 | | 45x+72=20x-4 | | 5x+3x+2+130=180 | | 7x-42=3x+6 | | V²+9v+19=0 | | 5x+2(-7x+4)=-46 | | (p/4)-4=9 | | 5=-2v+9 | | 64=32^x+1 | | 3x-65=2x+5 | | x+8+2x-8+4x-24=360 | | −3(2b−2)=48 | | 4^x-2=16^3x | | 6c+14=5c+4+9c= | | -3=-3x-7(-2x-9) | | 32x²−18=0 | | 32x2−18=0 | | 96+2(x)=80-3(x) | | s+4s+3s-2s-4s=14 | | x+13/5=51 | | 10r-2r-4r=12 | | -7x-7(-7x+3)=231 | | 6x+11x-90=-5 | | −2(4u−5)=34 | | -11u+13u+-6u+-11u+16u=-3 | | 25x-9x=80 | | 17y+4y-20y=8 | | 19r+5r-13r-5r=12 | | -5a+7=37 |